1992
DOI: 10.1164/ajrccm/145.4_pt_1.918
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterization of the Cellular Infiltration in Asthmatic Bronchi

Abstract: Bronchial biopsies obtained from 16 asthmatic patients and six normal subjects were analyzed by immunohistochemistry. In the asthmatic patients, the total numbers of macrophages infiltrating the airway mucosa were increased. Many of the macrophages had the phenotypic characteristics of blood monocytes. HLA Class II antigen was expressed on infiltrating cells and airway epithelial cells. In biopsies from the asthmatics there was a significant increase in activated eosinophils, but not in neutrophils. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(119 citation statements)
references
References 13 publications
7
111
1
Order By: Relevance
“…The lymphocytes are essentially all T-cells, and show increased activation compared to controls [11][12][13]15]. In the present study, we have demonstrated that lymphocyte numbers are increased both in cartilaginous and membranous airways although cell counts increase with airway size.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The lymphocytes are essentially all T-cells, and show increased activation compared to controls [11][12][13]15]. In the present study, we have demonstrated that lymphocyte numbers are increased both in cartilaginous and membranous airways although cell counts increase with airway size.…”
Section: Discussionsupporting
confidence: 53%
“…Increased numbers of polymorphonuclear cells (mainly eosinophils) and mononuclear cells (mainly lymphocytes) have been identified at autopsy in the airways of patients dying of asthma [1][2][3] and in patients with less severe asthma, by use of bronchoalveolar lavage (BAL) [4][5][6][7] and biopsy of proximal airways [7][8][9][10][11][12][13][14][15]. Immunohistochemical techniques have identified the CD4+ subset of T-lymphocytes in the airways of patients with asthma, and have demonstrated that these lymphocytes and eosinophils express markers of functional activation to a greater extent than those from nonasthmatic subjects [11,12,15,16].…”
mentioning
confidence: 99%
“…Endobronchial biopsy has been widely used as a research tool to assess airway inflammation in asthma [3,4,[6][7][8][9][10][11][12][13][14][15][16]22]. Its use as a tool in clinical research has recently become the subject of review [20].…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy studies of airway inflammation have generally used only two or three biopsies per case to enumerate a particular cell type [3,4,[6][7][8][9][10][12][13][14][15][16], and have often relied on 2D cell profile methods, expressing density as cells per area [4,[8][9][10][11][12][14][15][16].…”
Section: Inflammation In Bronchial Biopsies ML Carroll Et Almentioning
confidence: 99%
See 1 more Smart Citation